2021
DOI: 10.1021/acs.analchem.1c02529
|View full text |Cite
|
Sign up to set email alerts
|

TEPP-46-Based AIE Fluorescent Probe for Detection and Bioimaging of PKM2 in Living Cells

Abstract: Pyruvate kinase (PK) M2 (PKM2), a glycolytic enzyme, is a hallmark of different types of tumors and plays a significant role in the Warburg effect. However, there is no fluorescent probe for PKM2 that has been reported yet. In this study, TEPC466, a novel TEPP-46-based aggregation-induced emission (AIE) probe for the detection of PKM2, was designed, synthesized, and fully characterized by 1H NMR, 13C NMR, and high-resolution mass spectrometry. When the fluorescent agent, coumarine, was conjugated to TEPP-46, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The PKM gene encodes PKM1 and PKM2 through selective splicing ( Chen k et al, 2021 ; Itoyama et al, 2021 ). PKM1 is expressed in normal differentiated tissues ( Zhong et al, 2021 ), while PKM2 is expressed in highly proliferative cells such as embryonic cells, stem cells and tumor cells ( Wang et al, 2021 ). Physiologically, PKM1 exists as a tetramer, while PKM2 can exist as a tetramer or a dimer ( Hu et al, 2020 ; Rai et al, 2020 ).…”
Section: Glucose Metabolism In Neoplastic Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…The PKM gene encodes PKM1 and PKM2 through selective splicing ( Chen k et al, 2021 ; Itoyama et al, 2021 ). PKM1 is expressed in normal differentiated tissues ( Zhong et al, 2021 ), while PKM2 is expressed in highly proliferative cells such as embryonic cells, stem cells and tumor cells ( Wang et al, 2021 ). Physiologically, PKM1 exists as a tetramer, while PKM2 can exist as a tetramer or a dimer ( Hu et al, 2020 ; Rai et al, 2020 ).…”
Section: Glucose Metabolism In Neoplastic Cellsmentioning
confidence: 99%
“…Han et al, demonstrated that miR-383 regulates LDHA expression in OC cells, impeding glycolysis, cell proliferation and invasion ( Han et al, 2017 ). Tumor glycolytic activity is enhanced to adapt to ischemic and hypoxic environment by inducing an energy metabolic switch as the metabolic basis of its hypoxia tolerance ( Wang et al, 2021 ). This process activateshypoxia-inducible factor-1 (HIF-1), a widely present dominant oxygen regulator in mammals, triggers various biological events, including glycolytic activation and tumorigenesis ( Favier et al, 2015 ; Moldogazieva et al, 2020 ).…”
Section: The Regulatory Mechanism Of Ncrnas In the Glycolysis Of Ovar...mentioning
confidence: 99%
See 3 more Smart Citations